Effect of trade openness on economic growth within BRICS countries: an ARDL panel approach - Dekkiche, Djamal; Leila, Ouled Brahim (Anali Ekonomskog fakulteta u Subotici, 2024)
This paper investigates the connection between trade openness and economic growth in the BRICS countries (Brazil, Russia, India, China, and South Africa) using an autoregressive distributed lag (ARDL) panel approach. The study aims to shed light on the importance of international trade in fostering economic growth, particularly for developing countries. Using a comprehensive panel dataset and advanced econometric techniques, we assess the long-term equilibrium relationship between trade openness and economic growth in the BRICS context. The findings indicate a positive and significant impact of trade openness on economic growth, emphasising the need for policies promoting trade liberalisation and attracting foreign direct investment. This study contributes to the existing literature by offering empirical insights into the specific dynamics of trade openness and economic growth within the BRICS countries.